Genetic mutations, regression of Achilles tendon thickness, and cardiovascular events among patients with familial hypercholesterolemia. (January 2022) - Tada, Hayato; Okada, Hirofumi; Nohara, Atsushi; Takamura, Masayuki; Kawashiri, Masa-aki
Abstract: Background and aims: Achilles tendon thickness (ATT) can be regressed through LDL-lowering in patients with familial hypercholesterolemia (FH). We aimed to determine factors associated with regression of ATT and its role in development of major adverse cardiovascular events (MACE). Methods: Patients with clinically diagnosed FH (N = 1, 050, male/female = 490/560) were retrospectively assessed. FH-related gene mutations and ATT data using X-ray were collected. Multivariable linear regression analysis was exploited to test the factors associated with deterioration of ATT. Cox proportional hazards models were used to assess factors associated with MACE, including cardiovascular death and acute coronary events. Results: The median follow-up period was 12.6 years. FH-linked mutations were identified in 777 patients. During the follow-up period, 113 MACEs were observed, and median ATT was regressed from 8.7 to 8.5 mm. We found that there was more significant positive correlation between cholesterol-year score and ATT among patients with FH-related gene mutation ( p  < 2.2 × 10 −16 ; Spearman's r = 0.42). Multivariable linear regression analyses revealed that age (standardized coefficients [SCs] = 0.307, 95% confidence interval [CI] = 0.241–0.373), hypertension (SCs = 0.069, 95%CI = 0.001–0.138), and diabetes (SCs = 0.059, 95% CI = 0.003–0.115) were positively correlated with changes in ATT (progression). Baseline ATT (SCs = −0.474, 95%CI = −0.535–0.413) and FH-related mutations (SCs = −0.058, 95%CI = −0.091–0.024) were negatively correlated with changes in ATT (regression). Considering this confounding factors, regression of ATT was significantly associated with reduced MACE (hazard ratio [HR] = 0.67, 95%CI = 0.51–0.89, per 1.0 mm). Conclusions: Assessed ATT condition and presence of FH-linked gene mutations represent diagnostic values and risk stratification information among patients with FH. Graphical abstract: Image 1 Highlights: Age, hypertension, and diabetes were associated with Achilles tendon thickness (ATT) progression. Degree of ATT and familial hypercholesterolemia (FH)-related mutations were associated with regression of ATT. ATT regression was significantly associated with better cardiovascular disease prognosis.